PSIHOLOGIA SĂNĂTĂŢII CA DOMENIU ŞTIINŢIFIC DE FUNDAMENTARE ŞI VALORIFICARE A CONDUITELOR PRO-SĂNĂTATE ÎN CONTEXTUL EDUCAŢIEI PENTRU SĂNĂTATE A LICEENILOR - USM ADMIN (Moldova State University, 2009)
The present article reflects a scientific study applicative nature of analyzing conditions, life style and principles of health education for high school students. Defining personal goals, beliefs about health training models have been undertaken in the formative experiment. The authors stated and defined concepts: healthy lifestyle and healthy style. The article contains an analysis of health psychology principles in the context of finding experimental results compared with the preliminary experiment, focused on the analysis and interpretation of Health Study and Youth Development (2005). Here are elucidated strategies and methods of health education for teenagers in conjunction with family education.